Socio-economic transformation of the local community as gentrification’s implication in DKI Jakarta Province - Dewi, Santy Paulla (Jurnal Teknik Sipil dan Perencanaan, 2017)
Jakarta has a rapid development which attracts newcomers to come and live in. Hereinafter, the newcomers look for the house which in accordance to their income and preferences. They chose inner city kampong for residing and their existence displacing the Betawi people as the local community. The newcomers’ presence led displacement and transformed the neighbourhood. Likewise, they had also influenced in the socio-economic transformation related with education, women worker, community relationship, and lifestyle.